3D Printing as an element of teaching—perceptions and perspectives of teachers at German schools - Thyssen, Christoph; Meier, Monique (Frontiers in Education, 2023)
Digital technologies that are very close to the teacher's analogue field of activity, such as digital presentation, are increasingly taking place in the classroom, while digital, innovative technologies (e.g., 3D Printing) lacking such equivalents are used much less. Although such technologies are associated with more intense methodological and didactic changes, little is known about the extent to which 3D Printing is being used in German schools and how it is changing teaching and perspectives, which complicates the design of education and training measures. The use of such innovative technologies in the classroom is decisively influenced by the openness and acceptance of the teacher towards student-centered forms of learning and these technologies. The aim of the present study was to find out what expectations teachers (already) have about the use and potential of 3D Printing in the classroom and to what extent these are related to personal and/or external factors (e.g. 3D printers available in the school, number of STEM subjects). Therefore, an online-based questionnaire study was conducted with teachers in Germany (N = 100) who had different experiences with 3D Printing. The evaluation is based on descriptive, inferential and correlative analyses. Almost half of the teachers are equipped with 3D printers in their schools, while their use is even less widespread. In the perceptions of 3D Printing in the classroom from a methodological and didactic perspective, among other things, differences were revealed between teachers with different expertise in the knowledge and use of 3D Printing. In particular, the use of 3D Printing technology in their own lessons leads to a broader conception, especially with regard to the promotion of competencies. The results suggest theoretical models describing how to integrate 3D Printing into the classroom and concepts for 3D Printing trainings.